Aldehyde dehydrogenase 2 activation in heart failure restores mitochondrial function and improves ventricular function and remodelling. (9th May 2014) - Gomes, Katia M.S.; Campos, Juliane C.; Bechara, Luiz R.G.; Queliconi, Bruno; Lima, Vanessa M.; Disatnik, Marie-Helene; Magno, Paulo; Chen, Che-Hong; Brum, Patricia C.; Kowaltowski, Alicia J.; Mochly-Rosen, Daria; Ferreira, Julio C.B.
Abstract: Aims: We previously demonstrated that pharmacological activation of mitochondrial aldehyde dehydrogenase 2 (ALDH2) protects the heart against acute ischaemia/reperfusion injury. Here, we determined the benefits of chronic activation of ALDH2 on the progression of heart failure (HF) using a post-myocardial infarction model. Methods and results: We showed that a 6-week treatment of myocardial infarction-induced HF rats with a selective ALDH2 activator (Alda-1), starting 4 weeks after myocardial infarction at a time when ventricular remodelling and cardiac dysfunction were present, improved cardiomyocyte shortening, cardiac function, left ventricular compliance and diastolic function under basal conditions, and after isoproterenol stimulation. Importantly, sustained Alda-1 treatment showed no toxicity and promoted a cardiac anti-remodelling effect by suppressing myocardial hypertrophy and fibrosis. Moreover, accumulation of 4-hydroxynonenal (4-HNE)-protein adducts and protein carbonyls seen in HF was not observed in Alda-1-treated rats, suggesting that increasing the activity of ALDH2 contributes to the reduction of aldehydic load in failing hearts. ALDH2 activation was associated with improved mitochondrial function, including elevated mitochondrial respiratory control ratios and reduced H2 O2 release. Importantly, selective ALDH2 activation decreased mitochondrial Ca 2+ -induced permeability transition and cytochrome c release in failing hearts. Further supporting a mitochondrial mechanism for ALDH2, Alda-1 treatment preserved mitochondrial function upon in vitro aldehydic load. Conclusions: Selective activation of mitochondrial ALDH2 is sufficient to improve the HF outcome by reducing the toxic effects of aldehydic overload on mitochondrial bioenergetics and reactive oxygen species generation, suggesting that ALDH2 activators, such as Alda-1, have a potential therapeutic value for treating HF patients.